ANALISIS DIKSI DAN GAYA BAHASA DALAM ALBUM PERDANA ANDMESH KAMALENG - Moh. Syamsul Ma’arif; Lana Saadatul Abadiah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
This study aims to describe: (1) the use of diction in Andmesh Kamaleng's first album; (2) the use of language styles contained in the songs of Andmesh Kamaleng's debut album. Researchers are interested in analyzing the diction and language style on Andmesh Kamaleng's first album because it has its own way or its own characteristics in conveying or composing a song. The object of this research is the first album from Andmesh Kamaleng which consists of 8 songs. The lyrics of the song by Andmesh Kamaleng contain 3 types of diction and 13 kinds of language styles. Diction is a choice of words that can distinguish precisely based on the nuances of meaning that arise from the idea to be conveyed. Language style is the use of words in speaking and writing in order to convince or influence a listener and reader. This research is a qualitative descriptive using content analysis method. The data source is a document in the form of song lyrics from Andmesh Kamaleng's debut album. The data collection techniques used in this study were the listening and note taking technique. Validating the data in this study using theoretical triangulation. The data analysis technique used in this research is flow analysis which includes three processes, namely: (1) data reduction; (2) Presentation of data; (3) Drawing conclusions. In the song lyrics of Andmesh Kamaleng's debut album, it contains three kinds of diction, namely diction which means denotative, connotative, and synonymy. For the language style used by the author, there are 3 kinds of language styles included in the lyrics of this song, namely: comparative language style, contradiction style, and repetition language style. The results of this study can be concluded as follows: (1) the use of word choices or diction in Andmesh Kamaleng's song lyrics, namely: 38 data denotative diction, 11 connotative diction, 11 synonymy diction, and 3 synonymy diction. The purpose of using denotative diction in a work is especially in Andmesh Kamaleng's songs so that the message conveyed by the writer can be understood by the audience; (2) the use of this language style consists of 13 types, namely: asonance as much as 46 data, alliteration of 26 data, anaphore of 18 data, personification of 10 data, tautotes with 2 data, apostrophe 5 data, epizeukis 9 data, hyperbolic 8 data, mesodilopsis 2 data, epanalepsis 1 data, metaphor 2 data, and zeugma with 2 data. Keywords: diction, language style